GAMBARAN KEMAMPUAN BERHITUNG ANAK USIA 5-6 TAHUN DI TK ANANDA KECAMATAN SIAK HULU KABUPATEN KAMPAR - ', Yanti; Umari, Tri; Puspitasari, Enda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research was conducted in FY Ananda Siak Hulu, which will take place during the 3 months to plan implemented in January- April 2016, research was carried out as planned by Arikunto (2003) approaches and methods to be used is quantitative method. This study used quantitative methods, using survey. From the results of research and discussion, as was described in the previous chapters. So the conclusion of the study, namely: it can be seen that the overall aspects of numeracy skills of children observed apparently mostly in the category Emerging As expected, the percentage of 69%. This means that children are able to count the numbers 1-20 This means that the overall numeracy skills of children can be classified into categories Start Growing (MB), Growing expectations (BSH) and is growing very well (BSB). As a category, Start Developing indicators that recognize the many comparisons and a 55% increase. While the category Emerging As expected (BSH) Identify the number of objects with 1-20. As much as 80%. And know the meaning of the summation 1-20 with objects, of 74.1%., Counting objects of 1-20. 78.3%., While the category Growing Very Good indicator recognize and pronounce numbers 1-20 of 91.6%.